2007
DOI: 10.1200/jco.2007.25.18_suppl.5107
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of RAD001 in patients (Pts) with metastatic renal cell carcinoma (MRCC)

Abstract: 5107 Background: RAD001 is an oral mammalian target of Rapamycin (mTOR) inhibitor. Three mechanisms of anti-tumor activity; shuts down tumor response to nutrients and growth factors; cell cycle arrest at late G1 and anti-angiogenesis via VEGF. Molecular alterations in the mTOR modular pathway increase sensitivity in PTEN deficient tumors such as RCC. Endpoints: time-to-progression (TTP), response rate (RR), overall survival (OS), toxicity, and to assess changes in metabolic imaging utilizing CT-PET. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…An additional 19 patients had stable disease for Ͼ3 months. The toxicity profile seen in that trial was similar to what has been seen with other mTOR inhibitors [81].…”
Section: Everolimussupporting
confidence: 65%
“…An additional 19 patients had stable disease for Ͼ3 months. The toxicity profile seen in that trial was similar to what has been seen with other mTOR inhibitors [81].…”
Section: Everolimussupporting
confidence: 65%
“…Two phase II studies evaluated the use of everolimus compared with placebo in patients with metastatic renal cell carcinoma. 36,37 Both of these trials demonstrated superior efficacy in the progression of disease and set the stage for a large-scale randomized trial.…”
Section: Oncologymentioning
confidence: 99%
“…Pazopanib has completed phase I evaluation [60] and is being investigated in a phase II randomized discontinuation trial [61] and a phase III study. Everolimus has shown antitumour activity in pre‐treated patients with mRCC in phase II studies [46,62]. In a phase III trial in patients with mRCC who had progressed after treatment with RTK inhibitors, those treated with everolimus had a median PFS of 4.9 months (independent central review) compared with 1.87 months for placebo (HR 0.33, 95% CI 0.25–0.43) [63].…”
Section: Discussionmentioning
confidence: 99%
“…We present an overview of a treatment algorithm for mRCC, based predominantly on patient stratification according to previous treatment and prognostic risk groups (Fig. 1) [10,12–14,16,18,26,33,46]; other factors for consideration are discussed. The algorithm relies primarily on efficacy data due to the patient‐specific nature of tolerability, although this is a key factor in treatment choice [25].…”
Section: Treatment Algorithmmentioning
confidence: 99%